High-flavanol and high-theobromine versus low-flavanol and low-theobromine chocolate to improve uterine artery pulsatility index: a double blind randomized clinical trial. (2nd September 2017) - Bujold, Emmanuel; Leblanc, Vicky; Lavoie-Lebel, Élise; Babar, Asma; Girard, Mario; Poungui, Lionel; Blanchet, Claudine; Marc, Isabelle; Lemieux, Simone; Belkacem, Abdous; Sidi, Elhadji Laouan; Dodin, Sylvie
Abstract: Objective : To evaluate the impact of high-flavanol and high-theobromine (HFHT) chocolate in women at risk of preeclampsia (PE). Study design : We conducted a single-center randomized controlled trial including women with singleton pregnancy between 11 and 14 weeks gestation who had bilateral abnormal uterine artery (UtA) waveforms (notching) and elevated pulsatility index (PI). Participants were randomized to either HFHT or low-flavanol and low-theobromine (LFLT) chocolate (30 grams daily for a total of 12 weeks). UtA PI, reported as multiple of medians (MoM) adjusted for gestational age, was assessed at baseline and 12 weeks after randomization. Results : One hundred thirty-one women were randomized with mean gestational age of 12.4 ± 0.6 weeks and a mean UtA PI of 1.39 ± 0.31 MoM. UtA PI adjusted for gestational age significantly decreased from baseline to the second visit (12 weeks later) in the two groups ( p  < 0.0001) but no significant difference was observed between the groups ( p  = 0.16). Conclusions : Compared with LFLT chocolate, daily intake of HFHT chocolate was not associated with significant changes of UtA PI. Nevertheless, the improvement observed in both groups suggests that chocolate could improve placental function independently of flavanol and/or theobromine content.